👤

Bonjour pouvez-vous m'aider?

Développer et réduire les expressions suivantes :
A= 5(a+2)-(6a-7)
B= -b(3b+7)+(5-b)×B
C= -c(4+3c)-(9 -2c+6c)
D= -5d+5d(d-2)-6(7-3d)

Svp


Répondre :

Bonjour,


A= 5(a+2)-(6a-7)

A = 5a + 10 - 6a + 7

A = 5a - 6a + 10 + 7

A = a + 17


B= -b(3b+7)+(5-b)×B

B = - 3b² - 7b + 5b - b²

B = - 3b² - b² - 7b + 5b

B = - 4b² - 2b


C= -c(4+3c)-(9 -2c+6c)

C = - 4c - 3c² - 9 + 2c - 6c

C = - 3c² - 4c - 6c + 2c - 9

C = - 3c² - 8c - 9


D= -5d+5d(d-2)-6(7-3d)

D = - 5d + 5d² - 10d - 42 + 18d

D = 5d² - 5d - 10d + 18d - 42

D = 5d² + 3d - 42